Sport/leisure skill learning by adolescents with mild mental retardation: A four-step strategy - Yang, J.-J.; Porretta, D.L. (Adapted Physical Activity Quarterly, 1999)
Based on Singer's (1986) method, we investigated the effects of a four- step strategy (ready, look, do, score) on training, maintenance, and generalization of three closed skills (basketball free throw, overhand softball throw, and dart throw) by adolescents (M age = 17.2) with mild mental retardation (MR). A multiple baseline across skills design was used. Performances of 3 males and 3 females across these three skills were examined. Participants averaged a total of 46 sessions for the duration of the study. Results indicated that participants increased performance 18-56% across all three closed skills during the training phase. A total of 4 participants maintained performance on all three skills when reminders were present, and 2 decreased performance when the reminders were removed. All participants exhibited improved performance when a reinforcer was introduced. Moreover, 5 participants were able to generalize the four-step strategy to a different setting.
5 citations (Crossref) [2023-10-31]
Keywords: adolescent; article; clinical article; coping behavior; dept.hms; female; human; learning; leisure; male; mental deficiency; physical performance; skill; sport